Evaporation rates in a vital lake: a 34-year assessment for the Karaoun Lake. Issue 14 (17th July 2020) - Mhawej, Mario; Fadel, Ali; Faour, Ghaleb
ABSTRACT: The evaporation of water is an indispensable process in the earth water cycle. While high rates of evaporation made access to water resources harsher and costlier, monitoring the spatial and temporal variability of the evaporation rates, particularly in an open lake, is critical. Such information would enable to establish adequate management plans focusing on the sustainable use of available water resources. In this research, a vital lake in Lebanon, namely Karaoun or Qaraoun, was investigated. The importance of such reservoir lies in providing, solely, the required water for more than 500 000 households and 19 000 ha of agricultural lands. The evaporation rates were evaluated, both spatially and temporally, between 1985 and 2018 using the widely acknowledged Mapping EvapoTranspiration at high Resolution with Internalized Calibration (METRIC) system. This latter is based on 30 m. Landsat 4, 5, 7 and 8 satellite images. Main results emphasize the evaporation rates increase over the lake, particularly noticed since 2005. Between 1985 and 2018, the annual mean evaporation rate was 2.24 mm day −1 . More precisely, the annual mean evaporation rate has nearly doubled between 1985–1989 and 2014–2018 periods (i.e. 1.87 vs. 3.12 mm day −1 ). Mann-Kendall test and Sen's Slope estimates were produced to check the significance of the observed trends as well as to investigate the main driving factors behind this increase. Main causes were divided into natural (i.e. significant increase at α = 0.001 for temperatures and at α = 0.05 for solar radiations) and anthropogenic (i.e. deteriorating water quality) related factors. The most probable future scenario would highlight a fearful increase of 1°C in the next decade and an evaporation rate multiplied one and half times by 2038. These findings should help local management authority to mitigate water quality and turbidity effects, as well as to accurately estimate the water budget in an open-water lake. The concerned government should also benefit from these results to draw clear policies on how to conserve water resources with an increasing global warming trend. Such study could be portable to other regions where evaporation-related datasets are missing.